Institutional quality and private sector participation: theory and empirical findings - Rahel Schomaker (European Journal of Government and Economics (EJGE), 2014)
Through several conduits, sound institutional quality is pivotal for economic development, as there is evidence that stable democratic institutions, rule of law and sound governance structures in the administration are highly conducive to promote growth. Therefore, a high institutional quality is not only the end point, but also the starting point of a more sustainable development. In this paper we provide some theoretical considerations as well as empirical evidence, based on several regression analyses, that the quality of institutions in a wider sense, and governance, which includes not only the level of "politics" itself, but also the administrative level, is relevant not only for the macro-level of development (i.e. the increase of the national welfare and foreign investment), but also on a micro-level: A stronger participation of private enterprises in public service provision and the introduction of public-private partnerships depends to a high degree on the institutional quality. This is even more relevant as the improvement of public services and of core infrastructures can be seen as crucial multipliers for future growth.
Keywords: 330; good governance; institutional economics; private sector participationInstitutional quality; good governance; institutional economics; public-private partnerships; public goods